Macroeconomic Features of the French Revolution - Sargent, Thomas J.; Velde, François R. (Journal of Political Economy, 1995)
This paper describes aspects of the French Revolution from the perspective of theories about money and government budget constraints. We describe how unpleasant fiscal arithmetic gripped the Old Regime, how the Estates General responded to reorganize France's fiscal affairs, and how fiscal exigencies impelled the Revolution into a procession of monetary experiments ending in hyper-inflation.